Compound strip method for the analysis of continuous elastic plates - Puckett, Jay A., author; Gutkowski, Richard M., author; Colorado State University. Civil Engineering Department, publisher (Colorado State University. Libraries, 1983)
A finite strip method (FSM) is developed for the analysis of Iinear elastic flat plate systems which are continuous over deflecting supports. The approach presented incorporates the effect of the support elements in a direct stiffness methodology. The stiffness contribution of the support elements have been derived and are given In the form of strip matrices which are directly added to the plate strip stiffness matrix at the element level. This summation of plate and support stiffness contributions constitutes a substructure which is termed a compound strip. The validity of the compound strip method is demonstrated in several illustratlve problems which include single and muitlpanel plates continuous over flexible and rigid beams and columns. The FSM and finite element method (FEM) compare favorably for displacement and moment. The rate of convergence of the compound strip method was studied and results are given for a continuous multipanel system. The FSM is shown to be computationally more efficient than the FEM when maximum values for moment or deflection are required. The FEM exhibits favorable convergence characteristics in locations where the magnitudes of displacement and moment are relatively small.
Item deaccessioned after digitization.
Keywords: Plates (Engineering)